From crisis to peace the organic vegan way is the answer - Ching Hai (Love Ocean Creative International Company, 2010)
"This book contains unabridged excerpts from Supreme Master's talks at international conferences and gatherings with disciples, as well as from interviews with journalists."--Page ix.